Analisa Fungsi Hash Untuk Mendeteksi Otentikasi File Video Menerapkan Metode N-Hash - Harianja, Marjadi Hebert (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The problem with the video scope is that the video can be watched by unauthorized people if the video file needs to be secured with good security. So it is necessary to design a video player application and apply encryption and description to the designed application. N-HASH can only produce 16 bytes of ciphertext while the input is different, namely if the input is 4 bytes then the output is 16 bytes and if the input is 16 bytes then the output is 4 bytes. The results of detecting authentication of video files have a lot of data if in bytes the data is very difficult to encrypt with N-HASH.